Evaluación del paciente con trastorno de la marcha - Cerda A., Lorena (Revista Hospital Clínico Universidad de Chile, 2010)
A feature of humans is their ability to walk and their alteration limits the ability to perform activities of daily life Gait disorders have a major impact and have increased in frequency as a result of aging.This condition is usually caused by multiple factors; neurological and musculoskeletal etiologies are present in most patients.Health teams should identify gait problems, make a complete assessment and guide the etiological study. Most of the time the identification and treatment of the underlying condition will be sufficient to improves gait disorder. The aim of this paper is to review the physiological, pathophysiological and clinical basis of gait disorder to improve the assessment of these patients.